Synthesis and Characterization of a Magnetic Molecularly Imprinted Polymer by Suspension Polymerization for Selective Recognition of Dibenzothiophene from Gasoline Samples - Wanzhen Xu; Hui Li; Xiaoni Ni; Ningwei Wang; Yongsheng Yan; Chunxiang Li (Adsorption Science & Technology)
An effective method for the selective separation of dibenzothiophene (DBT) from gasoline samples using a magnetic molecularly imprinted polymer (MMIP) is described. The novel MMIP was synthesized by suspension polymerization using DBT as template. The morphology, magnetic and adsorption properties of MMIP were characterized by Fourier transmission infrared spectrometry, scanning electron microscopy, magnetic measurements, thermogravimetric analysis and nitrogen adsorption. Isothermal absorption of DBT, kinetics of absorption and adsorption selectivity on MMIP were then evaluated. Experimental results show that the adsorption behaviours of MMIP were well-described by the Freundlich isotherm and the pseudo-second-order kinetics. In addition, the synthesized adsorbent (MMIP) exhibited favourable affinity and selectivity for DBT over other competitive compounds.